Faktor-faktor yang Memengaruhi Tingkat Non Performing Financing dan Non Performing Loan pada Dual Banking System di Indonesia - Fathyah Isnaini; Sahara Sahara; Tita Nursyamsiah (AL-MUZARA'AH, 2019)
The value of non-performing financing Islamic banks in Indonesia based on OJK data on 2017 at 4.76%, which is greater than the percentage of non-performing loans in conventional banks at 2.59%, then that’s make a question why the percentage of Islamic banks is greater and what factors influence it. Data retrieval research is sourced from quarterly financial reports in the first quarter of 2012 to the third quarter of 2017 as many as 10 Islamic banks and 10 conventional commercial banks. This study aims to analyze the factors that affect the level of non-performing finance (NPF) and non-performing loans (NPL) in dual banking system Indonesia. Variable independent in this research are the growth of gross domestic product (GDP), inflation, BI rate, return on assets (ROA), financing to deposit ratio (FDR)/loan to deposit ratio (LDR), capital adequacy ratio (CAR), operating expenses on operating income (BOPO), and total assets while the dependent variable is NPF and NPL. The analytical method used to test the hypothesis is by panel regression analysis. The results of this study indicate that the sharia commercial banks have a significant influence on NPF including GDP, inflation, CAR, ROA, FDR, and BOPO. In conventional commercial banks significant factors include GDP, inflation, BI rate, CAR, LDR, BOPO, and total assets.